2007
DOI: 10.1063/1.2712804
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet light-emitting diodes with self-assembled InGaN quantum dots

Abstract: A photoluminescence study showed that the self-assembled InGaN quantum dots ͑QDs͒ provide strongly localized recombination sites for carriers and that the piezoelectric field-induced quantum-confined Stark effect ͑QCSE͒ is small because the height of QDs is too small to separate the wave functions of electrons and holes. The InGaN QD light-emitting diode ͑LED͒ showed an emission peak at 400 nm, and the peak was redshifted with increasing injection current, indicating a small QCSE. The light output power of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…Thus, there has been a growing effort over the past few years concerning intentionally grown InGaN QD based LEDs [59,60]. The investigated LED structure shows an onset voltage of 3.15 V at room temperature, and the QD ensemble EL band covers the spectral region from 2.2 to 2.6 eV.…”
Section: Electroluminescence Of Single Qdsmentioning
confidence: 99%
“…Thus, there has been a growing effort over the past few years concerning intentionally grown InGaN QD based LEDs [59,60]. The investigated LED structure shows an onset voltage of 3.15 V at room temperature, and the QD ensemble EL band covers the spectral region from 2.2 to 2.6 eV.…”
Section: Electroluminescence Of Single Qdsmentioning
confidence: 99%
“…To improve the emission efficiency of an UV LED, an alternate active layer with QDs has been used due to its enhanced exciton binding energy and carrier localization effect [48]. Recently, UV LEDs with self-assembled InGaN QDs grown in a strain-induced S-K mode have been reported for the first time by I. K. Park et al [49]. And in the same year, they demonstrated green LEDs with phase-separated In-rich InGaN QDs embedded in the InGaN active layer [50].…”
Section: High-brightness Uv Leds Have Great Advantages Inmentioning
confidence: 99%
“…Since these QDs are formed via strain relaxation during the growth of highly lattice-mismatched heteroepitaxy systems, controllability of the shape and size are limited by the total energy of the strained epilayer/substrate system. As a result, the height of InGaN QDs grown via a S-K growth mode is difficult to control without changing the lateral size [5], and is usually much smaller than the diameter, resulting in a small aspect ratio well below 1 [3][4][5][6]. Numerical calculations showed that the electron wave function in the QDs can penetrate significantly into the barrier for QDs with a small aspect ratio, resulting in reduced confinement of the electron wave function in the vertical direction and in an overlap integral between the electron and hole wave functions [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, InGaN-based self-assembled quantum dots (QDs) grown via the strain-induced Stranski-Krastanov (S-K) growth mode have attracted much attention for possible use in advanced light-emitting devices and quantum information applications [1][2][3][4]. Since these QDs are formed via strain relaxation during the growth of highly lattice-mismatched heteroepitaxy systems, controllability of the shape and size are limited by the total energy of the strained epilayer/substrate system.…”
Section: Introductionmentioning
confidence: 99%